2018
DOI: 10.3989/mc.2018.00717
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mix design on the size-independent fracture energy of normal- and high-strength self-compacting concrete

Abstract: Self-compacting concrete has a characteristic microstructure inherent to its specific composition. The higher content of fine particles in self-compacting concrete relative to the equivalent vibrated concrete produces a different fracture behavior that affects the main fracture parameters. In this work, a comprehensive experimental investigation of the fracture behavior of self-compacting concrete has been carried out. Twelve different self-compacting concrete mixes with compressive strength ranging from 39 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…In fact, Silica fume (SF) increases the cement cohesion and compressive resistance because it has a higher specific surface than metakaolin and cement, other studies confirmed these results and indicated that the use of metakaolin and Silica fume (SF) could increase the compressive resistance [9,[15][16][17]. Several experimental researches were conducted in recent years to investigate the effect of regular, volcanic, waste aggregate materials on different properties of self-compacted concrete [18][19][20][21]. Although there are acceptable studies about Silica fume (SF) and metakaolin, but there is only limited studied about the use of both of them simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Silica fume (SF) increases the cement cohesion and compressive resistance because it has a higher specific surface than metakaolin and cement, other studies confirmed these results and indicated that the use of metakaolin and Silica fume (SF) could increase the compressive resistance [9,[15][16][17]. Several experimental researches were conducted in recent years to investigate the effect of regular, volcanic, waste aggregate materials on different properties of self-compacted concrete [18][19][20][21]. Although there are acceptable studies about Silica fume (SF) and metakaolin, but there is only limited studied about the use of both of them simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Five different concrete mixes have been manufactured in this work and are designated as mix I, II, III, IV, and V. Table 1 shows the mix proportions of each concrete and the constituents used. The method that was proposed by Deeb and Karihaloo [13] for self-compacting normal and high-strength concretes, which was successfully was used in numerous researches, designed the mix proportion [14][15][16][17]. The compositions of the mixes have kept the cement and superplasticizer dosage constant.…”
Section: Methodsmentioning
confidence: 99%
“…This diagram is an important fracture property, especially when a numerical analysis of the fracture behaviour of concrete is needed, since it could model the fracture mechanism of material [44]. In this work, it has used an inverse analysis method that is based on the non-linear hinge model described in [14,45,46] to determine the parameters that defines the bilinear tension softening diagram (see Figure 5). It is worth noting that a qualitative analysis of the influence of the microstructure in the fracture behaviour of concrete can be completed from their corresponding bilinear softening diagrams, as was carried out in other authors [14,15,47,48].…”
Section: Bilinear Tension Softening Diagrammentioning
confidence: 99%
See 1 more Smart Citation
“…Another way to achieve a similar nucleation effect is to introduce 0.3% of C-S-H seeds into the pore medium, which promotes the formation of C-S-H bunches in the pore medium in place of the C 3 S stages [ 24 ]. On the other hand, the improvement in the pore medium accelerates the initial strength of mixtures, which can be quantified through microstructural investigations [ 25 ].…”
Section: Introductionmentioning
confidence: 99%